Housing valuation, wealth perception and portfolio composition: evidence from Portuguese households - Vale, S.; Camões, F. (16Th EBES Conference, 2015)
Numerous empirical studies find that portfolio composition varies significantly in risk and type of owned assets across households and that a large portion tends to show low diversification. Nevertheless, housing is the dominant asset in the households’ portfolios at the same time that it is an important consumption good. Assets demand and risky assets demand in particular are influenced by attitudes toward home property. Housing valuation while contributing to wealth perception and providing highly rated collateral may urge individuals to decide for new types of assets. In this paper we address the effects of housing investment valuation on the portfolio allocation of households. The analysis is based on the first wave of the Household Finance and Consumption Survey (HFCS) for Portugal that provides information about the household portfolio composition. We implement latent class models to define households groups with similar preferences while estimating heterogeneous portfolios. Broad categories of risky portfolios are defined and regressed against explanatory variables, amongst which we include the household wealth and household perceived wealth. Wealth is measured by the household net financial worth and perceived wealth by coefficients of housing valuation, a dummy for owner-occupied housing and past adverse changes. The model control variables include variables related to the head of the household such as their civil status, education, and employment status and variables that represent the household aggregate such as household income and the household structure. Our findings suggest strong heterogeneity in portfolio composition across Portuguese households. We also find that wealth is an important driver of portfolio composition.